Erratum: SHIDLOVSKIY, K.M., WATTERS, B.R. & WILDEKAMP, R.H. (2010) Notes on the annual killifish species Nothobranchius rachovii (Cyprinodontiformes; Nothobranchiidae) with the description of two new species. Zootaxa 2724, 37–57. - Shidlovskiy, K. M.; Watters, B. R.; Wildekamp, R. H. (Zootaxa, 2011)
(Erratum)